Pemodelan Bahaya Gempa Bumi Deterministik Berbasis Mikrotremor Berdasarkan Skenario Sesar Opak dan Dengkeng: Studi Kasus Kecamatan Depok, Sleman-Yogyakarta - Trisnowati, Yuni Dwi; Maharani, Yohana Noradika; Budi Nugroho, Arif Rianto; Kusumayudha, Sari Bahagiarti; Suharsono, Suharsono (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2025)
The Subdistrict of Depok, with the largest population in Sleman Regency, is a region that drives economic, social, and cultural development. This growth further increases the risk of earthquakes, given the presence of the active Opak and Dengkeng Faults. Therefore, an earthquake hazard analysis using the worst-case scenario from the Opak and Dengkeng Faults is necessary for disaster mitigation efforts. This study aims to model deterministic earthquake hazards based on microtremor data using the worst-case scenario from the Opak and Dengkeng Faults. A geophysical approach is employed in this research by applying the Horizontal-to-Vertical Spectral Ratio (HVSR) method based on microtremor measurements. The HVSR method characterizes local site effects that influence ground shaking during an earthquake. The earthquake hazard analysis at the ground surface is conducted using the Deterministic Seismic Hazard Analysis (DSHA) method, considering local site effects based on microtremor measurement data. The DSHA results indicate high Peak Ground Acceleration (PGA) values, primarily due to the influence of the Opak and Dengkeng Faults, which suggest a significant risk of damage. The findings of this study can serve as input for spatial planning and disaster risk reduction management, particularly in Depok District, Sleman Regency, Special Region of Yogyakarta.